THE SYMBOLIC MEANING OF COLORS IN HARRY POTTER AND THE DEATHLY HALLOWS - Susanti, Sri; Ezir, Ely; Anayati, Wan (JOURNAL OF LANGUAGE, 2024)
This study examines the symbolic meanings of colors in Harry Potter and the Deathly Hallows by J.K. Rowling, utilizing archetypal criticism and Carl Jung's theory of archetypal symbols. Through a qualitative analysis, the research explores how color functions as a tool for conveying deep thematic elements, enhancing the narrative, and reflecting the emotional and psychological states of the characters. Colors such as red, gold, green, black, white, and blue are shown to symbolize various abstract concepts, including friendship, bravery, immortality, power, love, and death. For instance, red and gold are associated with Gryffindor House values like courage and friendship, while green symbolizes both dark power and the protective love of Harry’s mother. Black is linked to death and darkness, and white signifies purity and sacrifice. By investigating these symbolic associations, the study reveals how Rowling employs color as a narrative device to enrich the reader's understanding of the characters' journeys and the larger themes of good versus evil, sacrifice, and the pursuit of truth. This research highlights the significance of color symbolism as an integral part of the storytelling in the Harry Potter series, providing deeper insights into the novel's thematic layers and the psychological motivations of its characters.